Simulation of a Transient Fault Controller for a Grid Connected Wind Farm with Different Types of Generators - Helmy Mohammed Abdel-Mageed; S.M. Sharaf; S.M. El_masry; M. El_harony (Institute of Advanced Engineering and Science, 2011)
This paper aims to simulate a wind farm model that includes wind turbine and three different types of generators , which are three-phase synchronous generator, three-phase squirrel-cage induction generator and three-phase doubly-fed induction generator ,these generators are the main machines that generally used in the field of wind energy generation. All generators are connected in parallel at the point of common coupling (PCC) and connected to the utility grid. This model is a simple representation of the actual model of Zafarana, which is the biggest wind farm in Egypt and further to use it in different kinds of simulations, and display the difference in response among all generators with the same power rating (500 kW) and subjected to the same operating conditions and faults. This paper describes the simulation of the different faults that occur along the transmission line of the power system such as single-line fault, line to line fault, double lines to ground fault, and finally three line faults. The response of the wind turbine and the different generators will be analyzed and discussed to compare the transient response of all generators at the different types of faults, where the fault period is selected to be 300 ms. The model is created in MATLAB software that enables the dynamic and static simulations of electric, electromagnetic and electromechanical systems. The machines are standard blocks in the software library.Keywords: transient faults, wind farm, simulation model.DOI: http://dx.doi.org/10.11591/ijpeds.v1i2.104